Spatial data warehouse: an analysis in tourism sector of west java province - Cholid Fauzi; Didik S Pribadi; Muhammad Riza Alifi (International Journal of Basic and Applied Science, 2023)
In the tourism business, the use of geospatial, sometimes known as geospatial information systems, is essential to the collection of data in various different ways. A collection of historical data and a set of tools to enable decision-making are both components of a geographic data warehouse. In this study, we investigate the requirements for developing a recommendation of spatial data warehouse (SDW) that makes advantage of the implementation the geographical data analysis and data visualization in tourism sector. Methodology of this research using qualitative analysis. The SDW Tourism sector technology model, on which work has been going on for some time, will be a driving factor in this study that aim to create a recommendation for integrated tourism data environments to assist with decision-making. It is possible to bring together in a single location not only non-spatial data but also spatial data, as well as applications that are now running on multiple platforms and databases. The output of this research makes a recommendation to construct a spatial data warehouse based on existing data, and diagram of how the data from the data warehouse will be used in the tourism sector.